Improving the reading skills of Jordanian students with auditory discrimination problems - Mukdadi, Afaf Abdullah; Batiha, Abdul-Monim; Ortega Martin, Jose Luis (International Journal of Advanced Nursing Studies, 2016)
Background: Some of the developmental problems facing students with difficulties in learning are those related to auditory perception which, in turn, can negatively affect the individual’s learning process.Aim: Evaluating a training program prepared to develop the auditory discrimination skills of students who suffer from auditory discrimination problems.Design: A quasi-experimental research design was used in this study. The study sample was divided into two equal groups: experimental and control.Participants and setting: The population of the study consists of students with learning difficulties from the second, third and fourth grades, whose ages range between 7-9 years old. Also involved were those enrolled in the resource rooms affiliated to the Jordanian Ministry of Education in Irbid province, amounting to (120) boy and girl students for the school year 2013- 2014.Results: The study showed that there was a significant difference in favor of the experimental group which indicated that the training program was effective. It helped the students with auditory discrimination problems to improve their reading skills. The results also showed a significant difference in favor of the students of older age in the experimental group. At the same time there were no significant differences in reading performance changes concerning gender.